Efektivitas Penggunaan Accurate Online dalam pelaksanaan program MBKM Magang Mandiri di PT Neo Farma Indonesia - Nabila Amelia Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article discusses the effectiveness of using Accurate Online software in supporting the accounting process during the implementation of the independent student internship program at PT Neo Farma Indonesia. Accurate Online as a cloud-based accounting information system is used to record financial transactions, manage stock, taxation, and prepare reports in real-time and integrated. This study uses a qualitative method through direct observation during the internship. The results of the observation show that the implementation of Accurate Online provides convenience in recording transactions, time efficiency, and strengthens the company's financial governance. Although there are technical constraints in the form of internet network quality, this does not significantly interfere with the effectiveness of the system. Thus, the use of Accurate Online is considered effective in supporting company operations and providing relevant work experience for students.